Compact broadband omnidirectional radiation pattern printed dipole antenna incorporated with split-ring resonators - Kedze, Kam Eucharist; Wang, Heesu; Park, Ikmo (IEEE Access, 2018)
A broadband, low-profile, compact, and cost-effective antenna consisting of a printed dipole loaded with split-ring resonators (SRRs) is presented. The antenna consists of two identical printed SRRs, each enclosing an arm of a printed dipole element. Each SRR and the center-fed half-wavelength dipole element are printed on the top and bottom sides of a thin dielectric substrate. The dipole is excited by a coaxial feed, while the SRRs are electromagnetically coupled to the dipole. The dipole, in conjunction with the SRRs, generates three resonant modes with stable omnidirectional radiation patterns. These resonances interact to provide broadband characteristics, that is, a measured impedance bandwidth covering 1.32-2.46 GHz for a reflection coefficient of less than -10 dB. The functionalities, mechanisms, and modes of operation of the composite antenna structure are discussed in relation to both the dipole and the SRRs. A prototype is fabricated and measured in order to validate the antenna design. It is computationally and experimentally confirmed that the antenna demonstrates broadband characteristics as well as a stable gain with non-deteriorating omnidirectional radiation patterns. The compact antenna, which has the overall dimensions of 9.6 mm × 74.4 mm × 0.508 mm ( 0.06λ × 0.469 λ × 0.0032λ at 1.895 GHz), has a measured fractional bandwidth of 60.31%, an omnidirectional radiation pattern with a gain greater than 1.8 dBi, and a radiation efficiency greater than 88% within a broad impedance bandwidth. The compact size, simple structure, and stable radiation properties of the antenna render it suitable for many wireless communication applications.
Keywords: Broad-band antenna; Broadband Communication; compact; Loaded antennas; Omnidirectional radiation pattern; Split-ring resonators (SRR); Broadband antennas; compact; composite antennas; dipole antennas; omnidirectional radiation pattern; split-ring resonator (SRR)